2013
DOI: 10.1093/ehjci/jet065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myocardial mechanics with three-dimensional speckle tracking echocardiography in heart transplant recipients: comparison with two-dimensional speckle tracking and relationship with clinical variables

Abstract: Examination of LV mechanics by 3D- and 2D-STE deformation parameters in heart transplant recipients yields significantly discordant results. 3D-STE-derived LSt is independently associated with NYHA class, suggesting a clinically important relationship between functional status and myocardial mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 24 publications
4
39
0
5
Order By: Relevance
“…20 Acquisition of 3D data sets and off-line analysis for speckle tracking were performed as previously described. 21,22 In summary, 3D data sets consisted of LV full pyramidal volumes, were acquired with the Matrix Array PST-25SX transducer from the apical position, and were created by the combination of 6 ECG-gated subvolumes. The off-line speckle tracking analysis was performed using the Wall Motion Tracking software (Toshiba) and blinded to late gadolinium enhancement (LGE) results.…”
Section: Echocardiographymentioning
confidence: 99%
“…20 Acquisition of 3D data sets and off-line analysis for speckle tracking were performed as previously described. 21,22 In summary, 3D data sets consisted of LV full pyramidal volumes, were acquired with the Matrix Array PST-25SX transducer from the apical position, and were created by the combination of 6 ECG-gated subvolumes. The off-line speckle tracking analysis was performed using the Wall Motion Tracking software (Toshiba) and blinded to late gadolinium enhancement (LGE) results.…”
Section: Echocardiographymentioning
confidence: 99%
“…UrbanoMoral et al reported that 3D-STE-derived, but not 2D-derived, global LS was independently associated with NYHA functional class in heart transplant recipients, which suggests a clinically relevant relation between functional status and 3D myocardial mechanics in heart transplant recipients. 53 In primary or secondary cardiomyopathies, late gadolinium-enhanced MRI has been widely used to identify myocardial characteristics, but 3D-STE also has the potential to provide additional information on myocardial characteristics. Matsumoto et al reported novel insights of the LV mechanics of dilated cardiomyopathy.…”
Section: Novel Insights From Clinical Studiesmentioning
confidence: 99%
“…They demonstrated that the systolic function of the endocardial fiber is mostly influenced by the LS, and the motion of the midwall fiber was significantly related to the RS [38]. Additionally, the midwall fiber is primarily responsible for the LV circular motion; therefore, the greatest influence on the CS and RS is the midwall fiber [39]. AS, composite motion of LS and CS, is a new concept that regional wall motion is quantified through the magnitude of deformation in an endocardial surface area [40].…”
Section: Myocardial Deformation Changes In Patients With Osamentioning
confidence: 99%